Semaglutide Treatment Effects on Liver Fat Content in Obese Subjects with Metabolic-Associated Steatotic Liver Disease (MASLD) - Dusilová, Tereza; Kovář, Jan; Laňková, Ivana; Thieme, Lenka; Hubáčková, Monika; Šedivý, Petr; Pajuelo, Dita; Burian, Martin; Dezortová, Monika; Miklánková, Denisa; Malínská, Hana; Svobodová Šťastná, Petra; et al. (Journal of clinical medicine, 2024)
Background: Metabolic-dysfunction-associated steatotic liver disease (MASLD) represents a major clinical complication of obesity. Methods: In this study, we used magnetic resonance (MR) methods to determine the effect of obesity treatment with semaglutide, a GLP-1 receptor agonist, on the liver fat content and selected metabolic variables. We investigated whether treatment would affect the acute response of liver fat to glucose and fructose administration and whether it would affect the fatty acid profile of VLDL-triglycerides. Sixteen obese non-diabetic men underwent a 16-week dietary intervention and 16-week treatment with subcutaneous semaglutide in a crossover design without a washout period. The order of the interventions was randomized. Results: After treatment, body weight of the subjects decreased by 5% and liver fat by a third, whereas dietary intervention had no impact on these parameters. The decrease in liver fat with semaglutide did not correlate with changes in body weight and other measures of adiposity and was unrelated to improved insulin sensitivity. Conclusions: The proportion of palmitic and palmitoleic acids in VLDL-triglycerides decreased after treatment, suggesting that the beneficial effects of semaglutide on liver fat are mediated by the suppression of de novo lipogenesis.
Keywords: insulin resistance; GLP-1 receptor agonists; semaglutide; obesity; metabolic-dysfunction associated steatotic liver disease; liver fat; nonalcoholic fatty liver disease; de novo lipogenesis